Pengaruh Green Accounting, Kinerja Lingkungan, Perputaran Total Aset terhadap Nilai Perusahaan, Profitabilitas sebagai Moderasi - Dilla Armeice; Ruswan Nurmadi; Liza Novietta (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
The purpose of this research was to analyze the role of profitability in moderating the relationship green accounting, environmental performance, and total asset turnover on firm value in the 2019-2023 food and beverage subsector. All food and beverage companies listed on the Indonesia Stock Exchange (IDX) in that period became the research population. The purposive sampling technique resulted in 80 companies. Analyzed were using Descriptive Statistics, Classical Assumption Tests, Hypothesis Testing, and Moderated Regression Analysis (MRA).The result show that green accounting has a negative and significant effect on firm value, while environmental performance has a positive and significant effect.Total asset turnover does not significantly affect firm value. Furthermore, profitability is proven to moderate the relationship between green accounting and environmental performance with firm value but does not moderate the effect of total asset turnover. Based on these findings, green accounting plays a role in influencing firm value, although it is not the primary factor determining investors assessments. The implementation of environmental performance is more widely perceived as a form of social responsibility and sustainability that enhances public trust and market value. Meanwhile, efficiency in asset utilization through total asset turnover is not considered a key determinant in increasing firm value.